Electricity Development and Opportunities to Reduce Carbon Dioxide Emissions in Morocco - El Ghazi, Firdaous; Sedra, Moulay Brahim; Akdi, Mahmoud (International Journal of Energy Economics and Policy, 2021)
Morocco, as many other countries in North Africa, is becoming vulnerable to climate change consequences. Its sulfur dioxide (SO2) and carbon dioxide (CO2) emissions are relatively high due to the electricity production, this sector is still heavily relying on coal. Morocco is also an emerging country, aiming to raise its economic development indicators and pursue a sustainable energy approach, facing additional challenges with industrial development and many coal infrastructures already in place. For the country, renewable energy is considered the most efficient pathway to decarbonize the electricity sector and reduce CO2 emissions. The main goal is to meet the growing need for electricity while preserving the environment. This study investigates the electricity sector in Morocco and its production sources, it highlights the limitations of the current model and gives an opportunity analysis to meet the carbon neutrality target. This study also provides some development axes and recommendations to accelerate and support the new energy vision. Keywords: Electricity production, Carbon Dioxide emissions, Energy transition, Coal, Renewable energy, Morocco. JEL Classifications: Q540, Q5, Q28, Q42 DOI: https://doi.org/10.32479/ijeep.11146